Can "the great tone split" in Thai be phonetically explained? - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1986)
This paper deals with the so-called "Great Tone Split" in Thai, which in most dialects has taken a course contrary to the general contention that initial voiced and voiceless consonants, if they have any conditioning effect on tonogenesis, will trigger a difference between a lower tone in the former case, and a higher tone in the latter case. On this background it is discussed to what extent tonogenesis of this type is at all phonetically explicable at present.